Identification of Dietary Preferences in Groupers from Raja Ampat Reefs Through Mitochondrial DNA Metabarcoding - Haqqy Rerian Erlangga; Raissha Amanda Siregar; Nurlita Putri Anggraini; Ester Restiana Endang Gelis; Erin Borbee; Christopher E. Lane; Inna Puspa Ayu; Beginer Subhan; Hawis Madduppa; Meutia Samira Ismet (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Groupers (Family Serranidae) are well known as top predators in the coral reef ecosystem. This family is one of the most important ecological organisms in the food web at Raja Ampat reefs. The aim of this study, therefore, was to investigate the food composition as well as the inter and intra-specific competition of two Serranidae species, including Epinephelus malabaricus and Epinephelus areolatus in Waisai, Raja Ampat. This study is expected to fill gaps on groupers food preferences. A total sample were collected at the fish landing site was 6 fish (2 sample of Epinephelus areolatus and 4 sample of Epinephelus malabacrius). DNA Amplification was performed using the COI mithocondrial gene marker (HCOI12198 and LCOI1490 primers). Bioinformatics and data analysis using QIIME 2 and R Software. This further comprised of α and β diversities. The results showed that Serranidae diet composition comprise of 13 species. Epinephelus malabaricus species demonstrated more diet composition varieties than Epinephelus areolatus. The most abundant diet found in all fishes’ gut samples was come from Scianidae family. The results indicate that there is an absence of any interspecific competition between the two species studied, due to a wide variation of diet composition. Conversely, intraspesific competitions existed amongst the Epinephelus malabaricus niches. This study highlighted DNA Metabarcoding application in trophic level and food web studies, as well as facilitating the development of information for ecological references.